2006
DOI: 10.1590/s0102-09352006000400021
|View full text |Cite
|
Sign up to set email alerts
|

Estimação de parâmetros genéticos para características de crescimento de ovinos Santa Inês utilizando modelos uni e multicaracterísticas

Abstract: RESUMOUtilizaram-se registros de pesos do nascimento aos 196 dias de idade de 927 cordeiros, filhos de 45 reprodutores e 323 matrizes de ovinos da raça Santa Inês, controlados de 1983 a 2000, com o objetivo de avaliar três modelos que consideraram ou não o efeito genético materno e a (co)variância entre os efeitos genéticos direto e materno, para estimar componentes de variância e parâmetros genéticos por meio de modelos uni e bicaracterísticas. Os componentes de (co)variâncias e os parâmetros genéticos direto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
11
2
13

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 12 publications
6
11
2
13
Order By: Relevance
“…However, effective genetic evaluation is dependent on the availability of accurate estimates of genetic parameters of the traits of interest, which depend on several factors. These factors include the quantity of data available, the statistical model applied, the method of estimation of (co)variance components, and the genetic parameters evaluated (SARMENTO et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, effective genetic evaluation is dependent on the availability of accurate estimates of genetic parameters of the traits of interest, which depend on several factors. These factors include the quantity of data available, the statistical model applied, the method of estimation of (co)variance components, and the genetic parameters evaluated (SARMENTO et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These values are lower than those observed in this study for the same breed. Sarmento et al (2006b) observed direct heritabilities of 0.20 and 0.00, respectively, for weights at birth and at weaning at 112 days old for Santa Inês breed. This value for birth weight is similar to that observed in this study.…”
Section: Resultsmentioning
confidence: 82%
“…Foram observados valores de pesos semelhantes aos encontrados em ovinos criados no Nordeste do Brasil (SARMENTO et al, 2006;SOUZA et al, 2006 No procedimento para as estimativas dos componentes de variância, houve indicação de convergência para todas as cadeias tanto para análises unicaracter quanto para análises bicaracter (Tabela 2).…”
Section: Resultsunclassified
“…Sarmento et al (2006) observaram correlações genéticas iguais a unidade entre os pesos ao nascimento, aos 56 e 112 dias. Lôbo et al (2009) observaram valores de correlações genéticas superiores as encontradas.…”
Section: Baneh Et Al (2010) Afirmaram Que Tanto Aunclassified
See 1 more Smart Citation